Systematic review of the scientific evidence of the pulmonary carcinogenicity of talc - Lynch, Heather N.; Lauer, Daniel J.; Thompson, William J.; Leleck, Olivia; Freid, Rachel D.; Collins, Justin; Chen, Kathleen; Ierardi, A. Michael; Urban, Ania M.; Cappello, Michael A.; Boffetta, Paolo; Mundt, Kenneth A. (Frontiers in Public Health, 2022)
We conducted a systematic review to assess the potential pulmonary carcinogenicity of inhaled talc in humans. Our systematic review methods adhere to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and incorporated aspects from the US Institute of Medicine (IOM) and several US EPA frameworks for systematic reviews. A comprehensive literature search was conducted. Detailed data abstraction and study quality evaluation, adapting the US Toxic Substances Control Act (TSCA) framework, were central to our analysis. The literature search and selection process identified 23 primary studies that assessed exposure to talc and pulmonary cancer risks in humans (n = 19) and animals (n = 3). Integrating all streams of evidence according to the IOM framework yielded classifications of suggestive evidence of no association between inhaled talc and lung cancer and pleural mesothelioma at human-relevant exposure levels.